Management of demand uncertainty in supply chain cost planning. Issue 4 (2015) - Mangal, Dharamvir; Gupta, Tarun Kumar
Cost effective supply chain management under various market, logistics and production uncertainties is a critical issue for companies in the current development. Reservations in the supply chain usually increase the variance of profits (or costs) to the company, increasing the likelihood of decreased profit. Demand uncertainty, in particular, is an important factor to be considered in the supply chain design and operations. To hedge against demand uncertainty, safety stock levels are commonly introduced in supply chain operations as well as in supply chain design. In this paper, the authors proposed the use of deterministic planning and scheduling models which incorporate safety stock levels as a means of accommodating demand uncertainties in routine operation.